Determination of basic soil properties and shear strength of Temerloh silty clay - Mohd Afifi, Mohd Salleh (2009)
The strength and stability of the soil surface need to be define before any construction begin. The purposes of this study are to obtain the basic characteristic and shear strength of silty clay at the some location in Temerloh district. It has low compressibility and most of the structure constructed on it usually will be affected especially in stabilization and settlement. In order to prevent that from happen, the engineering properties of silty clay must be determined before the beginning of any design work. In this study, some disturbed samples of silty clay were required, taken from 2 different locations which are Kg Buntut Pulau and Kg. Sanggang for soil identification, classification and properties test. For the determination of basic properties of that silty clay, a laboratory test of sieve analysis and Atterberg Limit were conducted in order to get the relationship between moisture content, liquid limit and plasticity index of every sample. Then, the Unconsolidated-Undrained test was choosed as the suitable method of Triaxial Test for determining shear strength parameters for the silty clay. From the result, the moisture content of the sample from both sites is 34.52% and 50.8% respectively. Meanwhile, for the Atterberg limit result, both site recorded the reading of 51.10% and 54.87% respectively for liquid limit and also 25.31% and 28.78% for the plastic limit. Then the value of plasticity index which obtain form the liquid and plastic limit is 25.79% and 26.09%. Then for the particle size distribution test, site A was recorded percentage of silt and clay as the highest with 51% and for same as for site B with 56% of silt and clay for the most dominant particle. The shear strength test results have clearly shown the weakness of Kg Buntut Pulau and Kg. Sanggang soil which are within soft clay soils strength with the average recorded value of 37.91kPa and 26.41kPa respectively. The data and result from this project can be used as a preliminary forecast for further investigation of soil properties and shear strength in the future construction and development.